Resveratrol-Enhanced Human Neural Stem Cell-Derived Exosomes Mitigate MPP+-Induced Neurotoxicity Through Activation of AMPK and Nrf2 Pathways and Inhibition of the NLRP3 Inflammasome in SH-SY5Y Cells - Ming-Chang Chiang; Yu-Ping Yang; Christopher J. B. Nicol; Tairui Chiang; Chiahui Yen (Life)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder primarily characterized by the loss of dopaminergic neurons in the substantia nigra. Mitochondrial dysfunction, oxidative stress, and neuroinflammation are recognized as critical pathological mechanisms driving neurodegeneration in PD. Exosome (Exo)-based therapies, particularly those derived from human neural stem cells (hNSCs), offer promising neuroprotective effects due to their ability to transfer bioactive molecules that modulate cellular processes. Resveratrol (RES), a polyphenolic compound with potent antioxidant and anti-inflammatory properties, has been shown to enhance the therapeutic potential of stem cell (SC)-derived Exos. This study investigated the neuroprotective effects of RES-treated hNSCs-derived Exos (RES-hNSCs-Exos) on SH-SY5Y cells exposed to 1-methyl-4-phenylpyridinium (MPP+), a neurotoxin commonly used to model Parkinsonian neurotoxicity. Treating SH-SY5Y cells with MPP+ led to significant reductions in cell viability, mitochondrial dysfunction, increased oxidative stress, and the activation of inflammatory pathways. Treatment with RES-hNSCs-Exos rescued SH-SY5Y cells from MPP+-induced toxicity by improving cell viability, enhancing ATP production, increasing mitochondrial biogenesis, and reducing reactive oxygen species (ROS) generation. The findings also demonstrated the increased expression of essential genes involved in mitochondrial biogenesis, such as PGC1α, NRF1, and Tfam, indicating improved mitochondrial function in the presence of RES-hNSCs-Exos. Further analysis revealed that these protective effects were mediated by activating the AMP-activated protein kinase (AMPK) and Nrf2 signaling pathways, which promoted mitochondrial health and reduced oxidative stress. Moreover, RES-hNSCs-Exos treatment suppressed neuroinflammation by downregulating NLRP3 inflammasome activation and reducing the secretion of pro-inflammatory cytokines IL-1β and IL-18. In conclusion, the results suggest that RES-hNSCs-Exos exhibit potent neuroprotective effects against MPP+-induced neurotoxicity by enhancing mitochondrial function, reducing oxidative stress, and inhibiting neuroinflammation. These findings highlight the potential of hNSCs-Exos as a novel therapeutic strategy for neurodegenerative diseases like PD, with RES as a valuable enhancer of Exos efficacy.